Ecthyma Gangrenosum due to Pseudomonas aeruginosa and Klebsiella pneumoniae without bacteremia - Sachin Manohar Shetty; Kikkeri Narayanshetty Naveen; Sharathchandra Bhimrao Athanikar; Zaheer Abbas Alikhan Pathan (Wolters Kluwer Medknow Publications, 2018)
Ecthyma gangrenosum (EG) is a rare cutaneous manifestation classically described for pseudomonal infection in immunocompromised patients. In addition to pseudomonas, numerous other infectious agents have been implicated to cause EG. Herein, we report a case of a previously healthy 45-year-old male patient who presented with multiple irregular deep ulcers of varying sizes with eschar. A clinical diagnosis of EG was made, and empirical antibiotic therapy was initiated. The culture material from the pus grew Pseudomonas aeruginosa and Klebsiella pneumoniae, both sensitive to piperacillin and tazobactam. Skin biopsy showed features of necrotizing vasculitis consistent with the diagnosis of EG.